2022
DOI: 10.1186/s12887-022-03735-y
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge and self-reported performance regarding the management of traumatic dental injuries and associated factors: a cross-sectional study

Abstract: Background Dental trauma is common among children. It has negative effects on a child’s quality of life. Parental knowledge, especially among mothers is an important factor for the long-term success of this emergency. This study aimed to investigate mothers’ knowledge and self-reported performance regarding the management of traumatic dental injuries and associated socio-demographic factors. Methods In this cross-sectional study, 277 mothers of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A previous study reported that level of education and occupation of mothers has a beneficial influence on their knowledge. Self-reported performance and mothers' educational levels were related (Momeni et al, 2022) Education will undoubtedly increase moms' awareness of dental trauma first-aid and their general capacity to manage emergencies. It appears that moms' lack of knowledge on how to manage and treat dental traumatic injuries has a negative impact on their performance, making them feel unable to do so.…”
Section: )mentioning
confidence: 99%
“…A previous study reported that level of education and occupation of mothers has a beneficial influence on their knowledge. Self-reported performance and mothers' educational levels were related (Momeni et al, 2022) Education will undoubtedly increase moms' awareness of dental trauma first-aid and their general capacity to manage emergencies. It appears that moms' lack of knowledge on how to manage and treat dental traumatic injuries has a negative impact on their performance, making them feel unable to do so.…”
Section: )mentioning
confidence: 99%
“…Traumatic dental injuries represent a significant public health concern, 1–4 and their prevalence among children is remarkably high 5–17 . The school environment represents a frequent setting for these incidents 7,8,10–12,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The school environment represents a frequent setting for these incidents 7,8,10–12,17,18 . Teachers play a crucial role, in as much as optimal long‐term prognosis depends on prompt implementation of appropriate immediate actions, 19 along with swift access to treatment, 20,21 and diligent post‐trauma follow‐up 14,12,13,15,18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations